Balancing in handstand on the floor - Hedbavny, P.; Sklenarikova, J.; Hupka, D.; Kalichova, M. (Science of Gymnastics Journal, 2013)
The contribution is a review study dealing with a handstand as one of the basic movement structures in artistic gymnastics. Balancing in this inverse position is a complex process based on physiological and physical principles. From physiological point of view the important results are from research dealing with function of vestibular apparatus, visual system, proprioception, central nervous system and motor units and their participation in balance maintaining. Another important question is a relationship between the strength of particular muscle groups and a level of balancing ability. Based on stabilometric measurements and 3D kinematic analysis of correcting movements equalizing the perturbations during a handstand we can distinguish several strategies of maintaining balance. Other important factors influencing the holding time in handstand position in gymnastics, mainly in tool disciplines, are a visual control and position of head.